Where am I? Who am I? The Problem of Location and Recognition in Helena Parente Cunha's Woman Between Mirrors - Joanne Gass (Studies in 20th & 21st Century Literature, 2005)
Helena Parente Cunha's novel, Woman Between Mirrors explores the many ways in which a dominant and domineering patriarchy can and does impose itself upon its subjects through what Louis Althusser calls interpellation. Parente Cunha's woman, a true twentieth-century heroine, faces her divided self—a self determined by ideology—and begins a quest which will end when she becomes an "I" before her shattered mirrors. But before that can happen, she must author herself, and, in the process of writing herself, she must overcome the demons of location and recognition. In the material sense, the woman must locate herself geographically, historically, socially, and physically. Existentially, she must locate herself as an acting, functioning, speaking, unified "I"—unified, in the sense that she is recognizable "in her entirety"; in order to do that, she must recognize herself in the multiple images of the mirror at the same time as she breaks the mirror images which her society reflects back to her—to be able to say "I" and to know that identity is not coherent and unified but that it has many facets, many voices, many responsibilities, becomes the object of her quest.
Keywords: Helena Parente Cunha; Woman Between Mirrors; women; patriarchy; Louis Althusser; interpellation; twentieth-century heroine; twentieth-century; divided self; ideology; location; recognition; material; geographically; historically; socially; physically; locate; Existentially; Existential; acting; functioning; speaking; unified I; unified; recognize; mirror; image of the mirror; image; breaking; break; reflect; society; voice; quest; identity